Macroeconomic policy adjustments due to COVID-19: Scenarios to 2025 with a focus on Asia - Roshen Fernando; Warwick J. McKibbin (Asian Development Bank Institute (ADBI), 2021)
This paper updates the analysis of the global macroeconomic consequences of the COVID-19 pandemic in earlier papers by the authors with data as of late October 2020. It also extends the focus to Asian economies and explores four alternative policy interventions that are coordinated across all economies. The first three policies relate to fiscal policy: an increase in transfers to households of an additional 2% of the GDP in 2020; an increase in government spending on goods and services in all economies of 2% of their GDP in 2020; and an increase in government infrastructure spending in all economies in 2020. The fourth policy is a public health intervention similar to the approach of Australia that successfully manages the virus (flattens the curve) through testing, contact tracing, and isolating infected people coupled with the rapid deployment of an effective vaccine by mid-2021. The policy that is most supportive of a global economic recovery is the successfully implemented public health policy. Each of the fiscal policies assists in the economic recovery with public sector infrastructure having the most short-term stimulus and longer-term growth benefits.
Keywords: C54; C68; F41; 330; COVID-19; pandemics; infectious diseases; risk; macroeconomics; DSGE; CGE; G-Cubed